Neutronic calculation of an axially heterogeneous ASTRID fuel assembly with APOLLO3®: Analysis of biases and foreseen improvements. (May 2018) - Faure, Bastien; Archier, Pascal; Vidal, Jean-François; Palau, Jean Marc; Buiron, Laurent
Highlights: Calculation schemes for axially heterogeneous CFV fuel assemblies are studied. Cross section collapsing over 2D radial geometries is the main source of biases. Consistent modelings coupled to conservative collapsing procedures are proposed. Significant improvements are found for both flux and eigenvalue. Abstract: Design of modern sodium fast reactors such as the French SFR project ASTRID are axially heterogeneous in order to maximize neutron leakage and therefore improve their natural behavior during transients. This feature is however challenging for neutronic calculations that usually rely on a first step based upon the generation of averaged cross sections over planar geometries. It is in particular the case of the APOLLO3® reference calculation route that is currently considered for SFR applications. This paper investigates the corresponding biases in the case of a 3D fissile assembly calculation and highlights the consequences of the fundamental mode assumption. It is shown that even though an acceptable global accuracy can be achieved, the flux distribution presents a slight axial drift. The homogenization and energy collapsing of anisotropic cross sections over radial geometries is pointed responsible for it. Several proposals are made to correct this inconsistency, leading to new calculation schemes and enhanced performances.